2015
DOI: 10.1186/s13071-015-0923-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of transmission of Babesia canis by Dermacentor reticulatus ticks to dogs treated orally with fluralaner chewable tablets (Bravecto™)

Abstract: BackgroundThe preventive effect of fluralaner chewable tablets (Bravecto™) against transmission of Babesia canis by Dermacentor reticulatus ticks was evaluated.MethodsSixteen dogs, tested negative for B. canis by PCR and IFAT, were allocated to two study groups. On day 0, dogs in one group (n = 8) were treated once orally with a fluralaner chewable tablet according to label recommendations and dogs in the control group (n = 8) remained untreated. On days 2, 28, 56, 70 and 84, dogs were infested with 50 (±4) B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 14 publications
(20 reference statements)
1
34
0
2
Order By: Relevance
“…Fluralaner is approved in many countries, including the United States and throughout Europe, to provide 12 weeks activity against several tick genera. The rapid onset of fluralaner acaricidal activity was shown to prevent the risk of Dermacentor reticulatus transmission of Babesia canis in a laboratory study [6]. Pharmacokinetic studies have shown that topically administered fluralaner is distributed systemically and fleas are exposed at the time of feeding [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fluralaner is approved in many countries, including the United States and throughout Europe, to provide 12 weeks activity against several tick genera. The rapid onset of fluralaner acaricidal activity was shown to prevent the risk of Dermacentor reticulatus transmission of Babesia canis in a laboratory study [6]. Pharmacokinetic studies have shown that topically administered fluralaner is distributed systemically and fleas are exposed at the time of feeding [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specific impacts of acaricides on tick feeding mechanisms and the consequent effects on tick borne pathogen transmission times were not measured in this study. Previous research has shown that each treatment administered in this study can prevent pathogen transmission under specific laboratory conditions [1820]. If there is a direct correlation between tick feeding time and pathogen transmission, then results of this study indicate that there will be differences between the ability of the acaricides tested to prevent pathogen transmission from ticks attached at the time of treatment.…”
Section: Discussionmentioning
confidence: 77%
“…The timing of pathogen transmission following attachment of an infected tick is variable, with a general suggestion that feeding for 24 to 48 h may be needed [4, 18]. Specific impacts of acaricides on tick feeding mechanisms and the consequent effects on tick borne pathogen transmission times were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…collars, spot-ons and orals) and modes of action (contact vs. systemic efficacy) (e.g. Elfassy et al 2001;Fourie et al 2013a;Honsberger et al 2016;Spencer et al 2003;Taenzler et al 2015Taenzler et al , 2016.…”
Section: Introductionmentioning
confidence: 99%